Exploring the Potential Impact of a Virtual Body Scan Meditation Exercise Conducted With Pet Dogs on Recipients and Facilitators - Kogan, Lori R.; Bussolari, Cori (Frontiers in Psychology, 2021)
Numerous recent studies have shown that COVID and the accompanying mandated lifestyle changes have resulted in significant negative effects on people’s mental health. To meet the increased need for mental health support, while also maintaining physical safety, a variety of telehealth services have been created or expanded. A body scan mindfulness program is an intervention that can easily be modified to be offered virtually. This study was designed to determine if a virtual body scan mindfulness exercise, with participants’ holding their dog or a pillow/blanket, could reduce their stress and anxiety as well as that of the facilitators. Significant differences in pre/post State Anxiety Assessment (STAI) scores for participants and facilitators were found. Additionally, participants and facilitators alike enjoyed the session more when the participants’ dogs were present. These results are discussed within the framework of the human animal bond and the potential of this form of intervention as a useful virtual tool for participants and facilitators alike.